1999
DOI: 10.1093/ajcn/70.4.536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with black currant seed oil on the immune response of healthy elderly subjects

Abstract: BCSO has a moderate immune-enhancing effect attributable to its ability to reduce prostaglandin E(2) production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 46 publications
3
54
0
4
Order By: Relevance
“…DISCUSSION PGE 2 is a proinflammatory eicosanoid, which has been indicated in pathogenesis of cardiovascular diseases, cancer, and inflammation. An age-related increase in PGE 2 production has been demonstrated in animal models (8,41,42) and in humans (43,44). Previously we showed that the increase in MØ PGE 2 production with aging contributes to a decline in T cell-mediated immune function.…”
Section: Effects Of Lps Treatment On Erk Jnk and P38 Kinase Activitmentioning
confidence: 74%
“…DISCUSSION PGE 2 is a proinflammatory eicosanoid, which has been indicated in pathogenesis of cardiovascular diseases, cancer, and inflammation. An age-related increase in PGE 2 production has been demonstrated in animal models (8,41,42) and in humans (43,44). Previously we showed that the increase in MØ PGE 2 production with aging contributes to a decline in T cell-mediated immune function.…”
Section: Effects Of Lps Treatment On Erk Jnk and P38 Kinase Activitmentioning
confidence: 74%
“…These observations are consistent with those of Johnson et al (23), who found no increase in serum GLA concentrations after 3 wk of supplementation with 1.5 g GLA/d but an increase in serum DGLA. Wu et al (24) recently reported a small increase in the proportion of GLA in total plasma lipids (from 0.5% to 0.8% by wt of total fatty acids) in healthy subjects given Ϸ700 mg GLA/d for 8 wk. The reason for the difference between the results of Wu et al (24) and those of the current study may relate to the nature of the lipid fraction studied: Wu et al reported the fatty acid composition of total plasma lipids, whereas we report the composition of the plasma phospholipid fraction.…”
Section: Discussionmentioning
confidence: 98%
“…Wu et al (24) recently reported a small increase in the proportion of GLA in total plasma lipids (from 0.5% to 0.8% by wt of total fatty acids) in healthy subjects given Ϸ700 mg GLA/d for 8 wk. The reason for the difference between the results of Wu et al (24) and those of the current study may relate to the nature of the lipid fraction studied: Wu et al reported the fatty acid composition of total plasma lipids, whereas we report the composition of the plasma phospholipid fraction. It is possible that GLA is found in higher proportions in the triacylglycerol and cholesteryl ester fractions than in the phospholipid fraction, in which case it would be more readily detected in total lipids than in purified phospholipids.…”
Section: Discussionmentioning
confidence: 98%
“…NS extract can enhance macrophages" innate immune functions that could control infectious diseases and regulate adaptive immunity 76 . Dietary supplementation with NSO improved the immune response of healthy old subjects, which is mediated by a change in the factors closely associated with T cell activation 77 .…”
Section: Anti-oxidant Anti-inflammatory and Immunomodulatory Effectsmentioning
confidence: 97%